Charge Transfer: Electronic Structure of Fullerene Heterodimer in Bulk‐Heterojunction Blends (Adv. Energy Mater. 7/2014). Issue 7 (May 2014) - Poluektov, Oleg G.; Niklas, Jens; Mardis, Kristy L.; Beaupré, Serge; Leclerc, Mario; Villegas, Carmen; Erten‐Ela, Sule; Delgado, Juan L.; Martín, Nazario; Sperlich, Andreas; Dyakonov, Vladimir
<x xml:space="preserve">Abstract</x> As reported by Oleg G. Poluektov, Jens Niklas, Vladimir Dyakonov, and co‐workers in article number 1301517, electronic coupling between fullerene cages in the dimer is influenced by their packing in the active organic photovoltaic (OPV) blends. This provides a new pathway to tune the electronic properties of the fullerene acceptors for better charge carrier generation efficiency in organic solar cells. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>